The world's oldest church: Bible, art, and ritual at Dura-Europos, Syria - Peppard, Michael (Synkrisis, 2016)
Michael Peppard provides a historical and theological reassessment of the oldest Christian building ever discovered, the third-century house-church at Dura-Europos. Contrary to commonly held assumptions about Christian initiation, Peppard contends that rituals here did not primarily embody notions of death and resurrection. Rather, he portrays the motifs of the church's wall paintings as those of empowerment, healing, marriage, and incarnation, while boldly reidentifying the figure of a woman formerly believed to be a repentant sinner as the Virgin Mary. This richly illustrated volume is a breakthrough work that enhances our understanding of early Christianity at the nexus of Bible, art, and ritual